QRM CONSIDERATIONS FOR MEDICINES REGULATORY AUTHORITIES - CHAVDA, VIVEK P. (Innovare Journal of Life Sciences, 2016)
Risk management principles are effectively utilized in many areas of business and government including finance, insurance, occupational safety, public health, pharmacovigilance, and by agencies regulating these industries. In regulatory perspective it is used to assist with resource allocation including, for example, inspection planning and frequency, and inspection and assessment intensity. It is also helps evaluate the significance of products; like quality defects, potential recalls and inspectional findings. It is also find its potential; appropriateness and type of postinspection regulatory follow-up To identify risks that should be communicated between inspectors and assessors to facilitate better understanding of how risks can be or are controlled (e.g., parametric release, Process Analytical Technology (PAT)). In short QRM has become a mandatory regulatory requirement towards healthcare organizations.